Size and age are important factors for marine sanctuaries: evidence from a decade of systematic sampling in a subtropical marine park. Issue 6 (8th October 2015) - Malcolm, Hamish A.; Jordan, Alan; Creese, Robert G.; Knott, Nathan A.
Abstract: Meta‐analyses of disparate studies suggest that size and age of a 'no‐take' area (marine sanctuary) can influence its ecological response to protection. Few studies, however, have been designed explicitly to test how these factors influence the abundance trajectories of key species within sanctuaries. Diver surveys on reef habitat were conducted within a subtropical marine park in eastern Australia, to test for differences in abundances of targeted fishes between sanctuaries differing in size and age and compared with fished zones. Four management zones were sampled: (i) small sanctuaries established 1991 (<15 ha of reef and <200 m wide); (ii) large sanctuaries established 2002 (>100 ha of reef and > 500 m wide); (iii) zones which allowed recreational fishing but not commercial fish trapping (>200 ha of reef); and (iv) zones which allowed both recreational fishing and commercial fish trapping (>200 ha of reef). Multiple sites in each management zone were sampled for selected taxa eight times during the austral winter from 2002 to 2012. Many of the targeted taxa examined were more abundant in large sanctuary sites within a few years of the establishment of protection compared with the small sanctuary sites and the fished sites. Red morwong Cheilodactylus fuscus increased in large sanctuaries but were more abundant in the older smaller sanctuaries throughout the study. Similar increases were not observed in fished zones. There was considerable variability among years not associated with management type, including a peak in abundance for several species in 2005 and reduced abundance of many taxa following a destructive storm in 2009. This study provides strong empirical evidence that size and age of 'no take' areas are important for fish, and indicates that larger sanctuaries can rapidly reach levels of fish abundance similar to smaller older sanctuaries. © 2015 Commonwealth of Australia.